Analysis of the Implementation of the International Safety Management (ISM) Code During Tank Cleaning to Optimize Safety and Security on MT. Gandawati - Daffani Tysa Lubis, Muhammad Naufal; Lestari, Elise Dwi; Eddi; Sitepu, Firdaus (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Tank cleaning on chemical tankers constitutes a high-risk maritime operation necessitating rigorous safety protocols to mitigate asphyxiation, toxicity, and explosion hazards. This study analyzes the implementation of the International Safety Management (ISM) Code during tank cleaning operations on board MT. Gandawati 1 to optimize occupational safety and security. Utilizing a descriptive qualitative approach, data were gathered through twelve months of direct participant observation, document analysis, and in-depth interviews with the ship’s command and crew. The results demonstrate a high level of structural compliance (88%), characterized by the systematic execution of risk assessments, enclosed space entry permits, and continuous atmospheric monitoring. However, a critical gap persists between regulatory requirements and operational reality, primarily driven by human factors. The study identified a 38.5% non-compliance rate regarding Personal Protective Equipment (PPE) usage, attributed to thermal discomfort and commercial time pressures. While the vessel achieved a zero-fatality record, the prevalence of near-miss incidents indicates that safety management has yet to be fully internalized into the onboard culture. The research concludes that optimizing safety requires transcending administrative compliance through enhanced behavioral supervision, ergonomic equipment upgrades, and the cultivation of a resilient safety culture.